2008
DOI: 10.1177/001979390806100306
|View full text |Cite
|
Sign up to set email alerts
|

Wage Growth and Job Mobility in the United Kingdom and Germany

Abstract: Using data from the British Household Panel Survey for 1991-99 and the German SocioEconomic Panel for 1984-99, the authors investigate job mobility and estimate the returns to tenure and experience. Job mobility was higher in the United Kingdom than in Germany. Returns to experience also seem to have been substantially higher in the United Kingdom, where the wage gain associated with ten years of labor market experience was around 80%, compared to 35% in Germany. The low returns to labor market experience in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 32 publications
6
85
1
5
Order By: Relevance
“…Turning to Germany, Dustmann and Meghir (2005) reported similar returns to general human capital accumulation for low-skilled workers, but somewhat higher returns for apprentices. In line with my findings, Dustmann and Perreira (2005) concluded that returns to experience for the low-and high-skilled are higher than for apprentices.…”
Section: Comparison With Existing Literaturesupporting
confidence: 82%
“…Turning to Germany, Dustmann and Meghir (2005) reported similar returns to general human capital accumulation for low-skilled workers, but somewhat higher returns for apprentices. In line with my findings, Dustmann and Perreira (2005) concluded that returns to experience for the low-and high-skilled are higher than for apprentices.…”
Section: Comparison With Existing Literaturesupporting
confidence: 82%
“…[33] find evidence for increasing polarisation for Germany; Machin for UK [34]; Ref. [35] for Portugal; both [36,37] for Europe.…”
Section: The State Of the Artmentioning
confidence: 99%
“…Our estimated return to potential experience is lower than estimates for the USA, UK, France, and Germany. Indeed, within these developed countries, estimated returns to potential experience range from 25 to 82 % (Altonji and Williams, 2005;Dustmann and Pereira, 2007;Beffy et al, 2006). Since Lagakos et al (2012) find that the returns to experience are lower in developing countries, it is plausible that our relatively low estimate of 13 % reflects differences between a developing country and developed countries.…”
Section: Resultsmentioning
confidence: 99%